(3cQhe YQhT GdJgGfi aj GdcdGe Ydi UdhGJ GHf eTjT GdOGfis
(3ChdgG (B:s
(3GdMeO ddg GdYGdi GdeMehO hHcd GdeMGeO GdYdjI hGdUdGI hGdSdGe Ydi GdfHi GdeMehO Phi GdebGUO GdSfjI hSejJg cQhe YQjT GdJgGfi ai GdcdGe Ydi UdhGJ Hf eTjT GdOGfi s
(3BNQgG (B:s
(3hcfJ CQi GdHTQi ai hLgg GdTQja JQi aYedJ Gfg hbY efg Udi Gddg Ydjg hSde Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs